2009
DOI: 10.1111/j.1469-185x.2008.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic ecology ten years after a call for more laboratory experiments

Abstract: About 10 years ago, reviews of the use of stable isotopes in animal ecology predicted explosive growth in this field and called for laboratory experiments to provide a mechanistic foundation to this growth. They identified four major areas of inquiry: (1) the dynamics of isotopic incorporation, (2) mixing models, (3) the problem of routing, and (4) trophic discrimination factors. Because these areas remain central to isotopic ecology, we use them as organising foci to review the experimental results that isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
755
4
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 822 publications
(797 citation statements)
references
References 141 publications
(266 reference statements)
18
755
4
20
Order By: Relevance
“…It is also important to recognise that the implications of such research reach beyond the practical goals of improved larviculture. There is a long history of application of carbon and nitrogen stable isotope analysis in trophic ecology (see recent review by Martínez del Rio et al, 2009). However, it is only in recent years that the generalised isotopic discrimination factors between consumers and their diets that are typically applied in such work have begun to be more fully underpinned by experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to recognise that the implications of such research reach beyond the practical goals of improved larviculture. There is a long history of application of carbon and nitrogen stable isotope analysis in trophic ecology (see recent review by Martínez del Rio et al, 2009). However, it is only in recent years that the generalised isotopic discrimination factors between consumers and their diets that are typically applied in such work have begun to be more fully underpinned by experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in larval studies, the relative contribution of elements provided in co-feeding regimes may be investigated, as well as the relative utilisation of dietary sources (eg protein) within compound feeds. The application of isotopic mixing models usually requires certain assumptions and conditions to be met in the experimental design (see review by Martinez del Rio et al, 2009). Not least of these is that larvae should be in isotopic equilibrium with their diet.…”
Section: Identification Of Nutrient Sourcesmentioning
confidence: 99%
“…The main reason for this trophic fractionation seems to be due to internal N metabolism, leading to 15 N enrichment in body proteins coupled with excretion of 15 N-depleted ammonia via urine (Balter et al 2006, Martínez del Rio et al 2009). There have been several recent revisions on differences between δ 15 N values of diet and consumers (Post 2002, McCutchan et al 2003, Vanderklift & Ponsard 2003, Vander Zanden & Fetzer 2007, Martínez del Rio et al 2009). Based on these revisions, it has been observed that nitrogen trophic fractionation depends on several aspects of both diet and the consumer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these revisions, it has been observed that nitrogen trophic fractionation depends on several aspects of both diet and the consumer. With regards to the former, the quantity and the quality of the protein is a key factor (Robbins et al 2005, Martínez del Rio et al 2009, Caut et al 2011). In the latter, the magnitude of nitrogen trophic fractionation depends on the type of tissue in question, as there are variations in turnover rates for different tissues (Newsome et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The low growth observed in larvae fed only on inert diet was reflected in a longer period of time to reach isotopic equilibrium, therefore contributions of nutrients at stages M 3 , PL 1 and PL 2 were estimated using ∆ 13 C values for PL 3 to PL 5 fed only inert diet. Assumptions associated with the use of isotope mixing models (see review by Martinez del Rio et al, 2009) to assess nutritional contributions from dietary sources were met in the present study. These include the similar elemental (carbon) composition in the food sources, quantified discrimination factors and avoidance of tissue isotopic routing by using whole animals for tissue analysis.…”
Section: Artemiamentioning
confidence: 99%